Innovation’s DNA in Postmodern Society Age - Barcellos, Ekaterina [UNESP]; Botura, Galdenoro [UNESP]; Inglesis, Lívia [UNESP] (Springer Nature, 2020)
The concept of innovation is still used as a synonym for creativity. Despite the overvaluation of creative ideas to achieve goals, logical systems have become even more essential for the digital society. A brief demonstration of the innovators’ DNA throughout history indicated that people with different skills had multifaceted elements, in a synergy that allowed them to glimpse different perspectives to extract unusual solutions. From Da Vinci to Bezos and Musk, innovators have an intelligence factor, added to the creative imagination assets but mixed with technological knowledge. The tangency between intelligence and creativity is defining to obtain innovation, confirmed from the past to the current context. Therefore, the innovative process requires specific skills, which combine logical factors with creativity. Especially in the postmodern context, the rational and technical base added to Design methodologies and strategic thinking provides greater and better resources to generate innovation.
Keywords: Creativity; Design methodology; Engineering and systems; Innovation; Intelligence